The lexical-semantic representation of horse coat colors in Turkic-Mongolian written monuments - Baigazh, Aizhan; Nurbayeva, Aida; Rustemova, Aigul (Turkic Studies Journal, 2026)
The article is devoted to a lexical-semantic description of the names of horse coat colors in Turkic and Mongolian written monuments as a significant component of historical lexicology and ethnolinguistics. In the context of nomadic culture, the horse functioned not only as an economic and military resource but also as an important socio-cultural symbol, which led to the formation of an extensive and highly differentiated system of linguistic description. The relevance of the research lies in the fact that, in the traditions of nomadic peoples, coat-color vocabulary performs not only a nominative function (i.e., the designation of color) but also serves as a means of precise identification of the animal, recording shades, patterns of color distribution, markings, and culturally conditioned evaluative meanings. The aim of the study is to determine the composition and structural principles of this microsystem, to describe nomination models, and to establish semantic regularities through a comparison of Turkic and Mongolian material. The empirical basis of the study consists of medieval written sources of the Turkic and Mongolian traditions representing various genres, including religious texts, narrative works, and lexicographic monuments that reflect different chronological and dialectal layers of the written tradition. Methodologically, the study relies on lexical-semantic and componential analysis, contextual analysis of usage, as well as comparative and historical-comparative approaches. Elements of etymological analysis are employed to clarify the internal form and motivation of individual lexical units. The analysis demonstrates that the system of coat-color terminology has a multilevel organization and includes: 1) basic color designations; 2) intermediate and shade coat categories; 3) terms denoting patterns of coloration distribution (piebaldness, spotting, etc.); and 4) names of markings and “portrait” features (e.g., a white spot on the forehead or the whiteness of the mane and tail). In many contexts, these features function as a type of coat-color designation in the identification of animals. Productive attributive naming models have been identified, as well as cases of polysemy and variation determined by the genre characteristics of the sources and by historical-dialectal fluctuations. The results demonstrate that coat-color vocabulary represents two interrelated levels: practical-descriptive and cultural-symbolic. On the one hand, it ensures precise classification and “portraiture” of the animal. On the other hand, it conveys notions of prestige, sacredness, and the normative image of the “proper” horse within traditional worldviews. In Turkic-Mongolian written monuments, coat-color designations constitute a culturally significant, multilevel system for naming and identifying horses. This system simultaneously performs descriptive and evaluative-symbolic functions. In Turkic texts, it is primarily realized as a system of classification, whereas in Mongolian texts, it functions as a narrative-evaluative system, reflecting the ethnocultural worldview of nomadic peoples.